ChemInform Abstract: Cyclodextrin and Phosphorus(III): A Versatile Combination for Coordination Chemistry and Catalysis. Issue 36 (September 2015) - Jouffroy, Matthieu; Armspach, Dominique; Matt, Dominique
Abstract Review: approaches to covalently bind the ubiquitous P(III) donor atom with a cyclodexrin cavity and coordination and catalytic properties of these cavity‐shaped liga nds; 152 refs.